2022
DOI: 10.3892/etm.2022.11462
|View full text |Cite
|
Sign up to set email alerts
|

Giant bladder stone: A case report

Abstract: Giant bladder stones are rare in younger patients. Herein, we report a case of acute renal failure in a 31-year-old male with a giant bladder stone. The patient presented with lower urinary tract symptoms and urinary retention with milky-white urine. An emergency suprapubic cystotomy was performed and an 11-cm oval, solid stone was removed. Post-operative creatinine levels progressively decreased to normal and the patient exhibited smooth urination and good recovery at follow-up. A comprehensive physical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…(1,2) There are different predisposing factors which are baseline cause for development of urinary bladder caliculi.Bladder outlet obstruction especially in aged patients due to benign prostatic hyperplasia and urethral stricture.Chronic urinary retension,recurrent urinary tract infection are also predisposing conditions for bladder calculi .These all may lead to concentrated residual urine and predispose to stone formation. (3,4) Bladder stones are mostly associated with renal or ureteral calculi, and they rarely ever occur without associated upper urinary tract calculi, as in our patient. There was also environmental and lifestyle associations of bladder stone formation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…(1,2) There are different predisposing factors which are baseline cause for development of urinary bladder caliculi.Bladder outlet obstruction especially in aged patients due to benign prostatic hyperplasia and urethral stricture.Chronic urinary retension,recurrent urinary tract infection are also predisposing conditions for bladder calculi .These all may lead to concentrated residual urine and predispose to stone formation. (3,4) Bladder stones are mostly associated with renal or ureteral calculi, and they rarely ever occur without associated upper urinary tract calculi, as in our patient. There was also environmental and lifestyle associations of bladder stone formation.…”
Section: Discussionsupporting
confidence: 56%
“…Urinary stones of up to 5 mm of diameter are known to pass spontaneously through the urinary tract; whereas those exceeding 7 mm of diameter almost always require surgical intervention. (2,3) The incidence of bladder stones among younger patients is low and that of large stones is rare. The formation of a large stone occurs over a long period of time and it may be complicated by concurrent serious infections, requiring open surgery for stone removal.This case report is a young man with huge bladder stone with preceding recurrent urinary tract infection and treated locally by oral medications.This delayed him to present to our set up atleast which had imaging services for better diagnosis of such cases.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder stones exceeding 100 g in weight are infrequent in contemporary urology, especially in developed countries such as those in Europe and the United States [ [10] , [11] ]. Several studies have showed largest bladder stone cases of largest bladder stones remains higher in developing countries and countries with ow income [12] , [13] , [14] , [15] , [16] . In Morocco, this case is the first recorded stone of giant bladder with 12 × 8 cm of size.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, postoperative complications and a long operation time. Open surgery for removing complete stones has shorter operation times [ 17 ].…”
Section: Discussionmentioning
confidence: 99%